Trends in Modern Typography Design: Visual Preferences on E-Commerce Platforms - Go, Eun Myeong; Mothelsang, Khaling (International Journal of Graphic Design, 2024)
In the digital era, typography design has become a fundamental element in shaping the visual identity and user experience of e-commerce platforms. Modern typography trends like minimalism, variable fonts, and responsive typography reflect a dynamic evolution aligned with user preferences and technological advancements. However, limited research addresses how typography influences users' visual preferences and engagement in the e-commerce context. This study aims to explore modern typography trends and their impact on user preferences while identifying elements that drive effective visual communication. To achieve these objectives, the research employs a mixed-method approach. A visual content analysis was conducted on typography used by leading e-commerce platforms, such as Amazon, Shopee, and Tokopedia, to identify prevailing design trends. A survey involving 150 active e-commerce users was conducted to understand their perceptions and preferences regarding typography design. Quantitative data from the survey were analyzed using statistical methods, while qualitative insights were interpreted to provide context. The results reveal that users prefer sans-serif fonts and minimalist designs due to their clarity, readability, and modern appeal. Variable fonts and dynamic typographic layouts were also noted for their ability to enhance engagement, though these trends appeal primarily to younger audiences. This study concludes that typography significantly influences user perception and interaction within e-commerce platforms. The findings contribute to the field of user experience design by offering actionable insights for designers and developers, aiming to create visually appealing and user-centered platforms.